Impact of electrolyte on the electrochemical performance of Lithium-ion half and full cells with Silicon film anodes. (10th August 2017) - Farmakis, F.; Elmasides, C.; Selinis, P.; Georgoulas, N.
Abstract: Amongst anode materials for lithium ion batteries, silicon's high theoretical capacity, environmental friendliness, low potential vs Li/Li +, material abundance and technological maturity, turn it to a strong candidate for the replacement of carbon-based anodes. In this work we studied the influence of various electrolyte solutions and additives to the silicon's stability over cycling. We have to use electrolyte solutions and additives that form a stable Solid Electrolyte Interphase (SEI) layer, which protects silicon's integrity and prolongs its cycle life. In this work, we present the experimental results of half and full cells with silicon anodes with various electrolytes and additives. It becomes obvious that the electrolyte solution plays an immense role to the formation of SEI layer and thus, the electrochemical properties of silicon anodes.